Influences of product and process parameters on selected quality attributes of heat-treated Philippine Orange (Dalandan) juice - Cayabyab, Jochelle Elysse C.
This study established predictive models for the individual and interactive influences of various combinations of process and product parameters namely, heating temperature, heating time, soluble solids (SS), and titratable acidity (TA) on the residual ascorbic acid (AA) content, and ascorbic acid loss (ΔAA) of simulated citrus juice (SCJ) systems using Response Surface Methodology (RSM). Polynomial models describing the individual and interactive influences of temperature, time, SS, and dilution rate on the Commission Internationale de l'Éclairage (CIE) color parameters of heated Philippine orange juice were also established using RSM. SCJs and Philippine orange juice samples were prepared according to the combinations generated by the Central Composite Rotatable Design of Experiment. Only the individual linear effects of temperature and time significantly (P<0.05) affected AA and ΔAA. The individual linear effects of SS and dilution rate significantly affected CIE L*, ΔL*, h°, Δh°, and ΔE* values. Furthermore, the linear influence of dilution rate on b*, Δb*, C*, and ΔC* were found to be significant; while CIE a* and Δa* values were significantly affected by the individual linear influences of SS and dilution rate, and the quadratic effect of SS. All validating systems for the predictive models for AA and ΔAA had acceptable predictive efficacy with accuracy factor (Af) ranging from 1.00 to 1.60. On the other hand, mathematical validation of the resulting models for the CIE color parameters showed that 152 out of 220 (69.09%) systems were predicted within the acceptable margin of error. The results reported in this work may be useful in the establishment of specific heat process schedules for unique products, for the preservation of product quality.